Novelties towards a phylogenetic infrageneric classification of Baccharis (Asteraceae, Astereae) - Heiden, Gustavo; Pirani, José Rubens (Phytotaxa, 2016)
Names of new taxa, new combinations and names at new rank are proposed for subgenera and sections in Baccharis to move towards a phylogenetic infrageneric classification of this New World genus. Two earlier segregated genera and two previously recognised sections are moved to the subgeneric rank (as B. subgen. Coridifoliae, B. subgen. Heterothalamus, B. subgen. Heterothalamulopsis, and B. subgen. Oblongifoliae). Three new combinations and/or names at new rank are proposed for the following sections: B. sect. Axillares (assigned to B. subgen. Baccharis), B. sect. Heterothalamulopsis (assigned to B. subgen. Heterothalamulopsis), and B. sect. Pluricephalae (assigned to B. subgen Coridifoliae). Four new sections are described to accommodate taxa not corresponding to any previously described section: B. sect. Andina and B. sect. Illinitae (assigned to B. subgen. Baccharis), B. sect. Bradeanae (assigned to B. subgen. Heterothalamus), and B. sect. Polifoliae (assigned to B. subgen. Molina). All taxa here recognized correspond to monophyletic groups based on highly supported clades in a recent molecular phylogenetic analysis.